EXPLORING LANGUAGE POLITENESS: : A CRITICAL ANALYSIS OF BARACK OBAMA’S 2020 "60 MINUTES" INTERVIEW - velizziano, diaz_1045 (Language Horizon: Journal of Language Studies, 2025)
The present research endeavors to examine the linguistic expressions of politeness that were utilized by Barack Obama in the course of his "60 Minutes" interview in the year 2020. This study examines the theoretical underpinnings, historical background, and pragmatic implications of politeness in language through the integration of seminal works of Brown and Levinson’s (1987) politeness universals, Watts, Ide, and Ehlich’s (2005) research on politeness in language, Locher and Watts’ (2005) politeness theory and relational work, Culpeper’s (2011) study on impoliteness, and Goffman’s (1967) investigation on face-to-face interactions. Through the examination of the interview transcript, this research illuminates the various politeness strategies employed by Obama, namely positive politeness tactics that prioritize solidarity and rapport, negative politeness tactics that acknowledge autonomy, and adroitly navigated face-threatening behaviors. The results indicate the efficacy of the politeness tactics employed by Obama in preserving favorable social interactions and controlling his public persona. The present study delves into the pragmatic implications of the language politeness strategies employed by the individual in question. Notably, this research elucidates how these strategies facilitate the individual’s navigation of power dynamics, as well as their ability to control their public image while engaging the audience. This research enhances comprehension pertaining to the language politeness prevalent in political discourse, while imparting discerning observations regarding the communicative maneuvers exercised by prominent personalities, such as Barack Obama.